Genetic Characteristics of CRF01_AE Among Newly Diagnosed HIV-1-Infected 16- to 25-Year Olds in 3 Geographic Regions of Guangxi, China. Issue 21 (May 2015) - Zhang, Jing; Shen, Zhi-Yong; Li, Zheng; Liang, Shu-Jia; He, Cui; Liang, Fu-Xiong; Feng, Yi; Li, Jian-Jun; Ruan, Yu-Hua; Zhou, Yue-Jiao; Shao, Yi-Ming; Xing, Hui; et al.
<x xml:space="preserve">Abstract</x> Abstract The aim of this study was to analyze the distribution of clusters and drug resistance of CRF01_AE among newly diagnosed, treatment-naïve HIV-infected teenagers and young adults in 3 major HIV-affected geographic regions of Guangxi Province, including the cities of Hezhou, Liuzhou, and Nanning. Samples were sequentially collected from newly diagnosed HIV-infected 16- to 25-year olds in these 3 regions from 2009 to 2013. The viral genome was extracted, and the partial pol gene was amplified and sequenced. Phylogenetic analyses were used to determine HIV-1 subtypes and CRF01_AE clusters. Transmitted drug resistance (TDR) mutations were identified using the 2009 WHO list of TDR mutations. A total of 216 sequences were obtained from CRF01_AE strains, which accounted for 83.1% of the 260 genotyped samples, of which 36 were from Hezhou, 147 from Liuzhou, and 33 in Nanning. Most (83.3%, 180/216) were from heterosexuals, followed by injection drug users (5.6%), homosexuals (4.2%), and unknown risk group (6.9%). Based on phylogenetic analyses by the maximum likelihood method, 5 distinct clusters (cluster 1–5) were identified with 213 (98.6%) sequences, whereas 3 (1.4%) sequences were ungrouped. In Hezhou, 88.9% (32/36) of CRF01_AE infections were caused by cluster 2, and 11.1% (4/36) were caused by cluster 1. In Liuzhou, 83.0% (122/147) of the CRF01_AE strains were found in cluster 1, 11.6% (17/147) from cluster 2, 1.4% (2/147) from cluster 3, 2.7% (4/147) from cluster 4, and 0.7% (1/147) from cluster 5. The distribution of CRF01_AE clusters was more even in Nanning than it was in the other 2 regions, with 18.2% (6/33) from cluster 1, 36.3% (12/33) from cluster 2, 9.1% (3/33) from cluster 3, 18.2% (6/33) from cluster 4, and 12.1% (4/33) from cluster 5. The most frequent TDR mutations were M46I (2) in the protease region and Y181C (2) from the reverse transcriptase fragment. Clusters 1 and 2 of CRF01_AE strains were prevalent in Liuzhou and Hezhou, respectively. However, multiple CRF01_AE clusters existed in Nanning. This can be partially explained by the high mobility of laborers in Nanning, the capital city of Guangxi. The prevalence of TDR was low.